The spinal headache in pregnant women - Kuczkowski, Krzysztof M (Nepal Journal of Obstetrics and Gynaecology, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Pregnant women are at particular risk of dural puncture (and the subsequent headache) because of sex, young age, and the widespread application of regional anesthesia. The incidence of epidural needle-induced post-dural puncture headache (PDPH) also known as spinal headache in pregnant women following dural puncture with a large bore needle has been reported to range 76-85%. Although a few measures have been proposed to prevent PDPH Intrathecal injection of saline, insertion of the epidural catheter into the subarachnoid space through the dural hole, none have been shown to work with certainty to date. This article reviews the latest developments aimed at prevention and treatment of this debilitating condition. Key Words: Labor analgesia; epidural, combined spinal epidural; complications, dural puncture, postdural puncture headache (PDPH); prevention. doi:10.3126/njog.v1i2.1486 N. J. Obstet. Gynaecol Vol. 1, No. 2, p. 4 - 9 Nov-Dem 2006